2013
DOI: 10.2478/s11756-013-0283-2
|View full text |Cite
|
Sign up to set email alerts
|

Coastal salt-marshes plant communities of the Salicornietea fruticosae class in Apulia (Italy)

Abstract: An overview of the salt-marsh herbland and scrub vegetation belonging to the class Salicornietea fruticosae Br.-Bl. et Tx. ex A. Bolòs y Vayreda 1950 in Apulia is presented. Data available from literature have been supplemented with original relevés performed in different locations of the Apulia region. On the basis of a total of 297 relevés, fifteen communities have been defined, according to the traditional phytosociological system based on dominant and/or diagnostic taxa. For comparison purposes, the salt-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 24 publications
1
15
1
Order By: Relevance
“…Adjacency rules are based on vegetation pattern and appear particularly effective in the case of coastal environments, due to the close correlation between ecological gradients and vegetation pattern. In the case of the study site Le Cesine, the observed spatial patterns are in accordance with the existing literature for central-southern Italian peninsula and Puglia region (Frondoni & Iberite 2002;Biondi & Casavecchia 2010;Cutini et al 2010;Sciandrello & Tomaselli 2014). Nevertheless, the complete expected zonation pattern is observed only where disturbance is not significant.…”
Section: Discussionsupporting
confidence: 89%
“…Adjacency rules are based on vegetation pattern and appear particularly effective in the case of coastal environments, due to the close correlation between ecological gradients and vegetation pattern. In the case of the study site Le Cesine, the observed spatial patterns are in accordance with the existing literature for central-southern Italian peninsula and Puglia region (Frondoni & Iberite 2002;Biondi & Casavecchia 2010;Cutini et al 2010;Sciandrello & Tomaselli 2014). Nevertheless, the complete expected zonation pattern is observed only where disturbance is not significant.…”
Section: Discussionsupporting
confidence: 89%
“…2013). Recently, a new locality of H. strobilaceum, situated in the southern part of the Italian Adriatic basin, at the mouth of River Carapelle in northern Apulia (Sciandrello & Tomaselli 2014), has been described. However, by observing the photos appearing in the publication it seems that it could be attributed to H. cruciatum.…”
Section: Taxonomic Aspects and Distribution In Italymentioning
confidence: 99%
“…which is very sensitive to dryness and is very rarely captured by pitfall trap because of its low mobility and scarce superficial activity. High species richness was found in Arthrocnemo-Juncetum subulati (AJs), Phragmitetum communis (Pc), and Agropyro scirpei-Inuletum crithmoidis (AsIc), which grows on salt clay soils humid for long time (Tomaselli et al 2011;Sciandrello & Tomaselli 2014). Arthrocnemo-Juncetum subulati (AJs) was the richest with 13 species, two of which, H. hirsuta and P. lamellatus, are purely halophilous species (see also Montesanto et al 2007) and one, C. elongata, is strongly hydrophilous and also has the highest aAD value (18.67).…”
Section: Abundance Of Isopods In Relation To Plant Communitiesmentioning
confidence: 99%